Atrial Fibrillation Risk and Discrimination of Cardioembolic From Noncardioembolic Stroke. Issue 5 (May 2020) - Khurshid, Shaan; Trinquart, Ludovic; Weng, Lu-Chen; Hulme, Olivia L.; Guan, Wyliena; Ko, Darae; Schwab, Kristin; Rost, Natalia S.; Al-Alusi, Mostafa A.; Benjamin, Emelia J.; Ellinor, Patrick T.; Anderson, Christopher D.; et al.
Abstract : Background and Purpose—: Classification of stroke as cardioembolic in etiology can be challenging, particularly since the predominant cause, atrial fibrillation (AF), may not be present at the time of stroke. Efficient tools that discriminate cardioembolic from noncardioembolic strokes may improve care as anticoagulation is frequently indicated after cardioembolism. We sought to assess and quantify the discriminative power of AF risk as a classifier for cardioembolism in a real-world population of patients with acute ischemic stroke. Methods—: We performed a cross-sectional analysis of a multi-institutional sample of patients with acute ischemic stroke. We systematically adjudicated stroke subtype and examined associations between AF risk using CHA2 DS2 -VASc, Cohorts for Heart and Aging Research in Genomic Epidemiology-AF score, and the recently developed Electronic Health Record–Based AF score, and cardioembolic stroke using logistic regression. We compared the ability of AF risk to discriminate cardioembolism by calculating C statistics and sensitivity/specificity cutoffs for cardioembolic stroke. Results—: Of 1431 individuals with ischemic stroke (age, 65±15; 40% women), 323 (22.6%) had cardioembolism. AF risk was significantly associated with cardioembolism (CHA2 DS2 -VASc: odds ratio [OR] per SD, 1.69 [95% CI, 1.49–1.93]; Cohorts for Heart and Aging Research in Genomic Epidemiology-AF score: OR, 2.22 [95% CI, 1.90–2.60]; electronic Health Record–Based AF: OR, 2.55 [95% CI, 2.16–3.04]). Discrimination was greater for Cohorts for Heart and Aging Research in Genomic Epidemiology-AF score (C index, 0.695 [95% CI, 0.663–0.726]) and Electronic Health Record–Based AF score (0.713 [95% CI, 0.681–0.744]) versus CHA2 DS2 -VASc (C index, 0.651 [95% CI, 0.619–0.683]). Examination of AF scores across a range of thresholds indicated that AF risk may facilitate identification of individuals at low likelihood of cardioembolism (eg, negative likelihood ratios for Electronic Health Record–Based AF score ranged 0.31–0.10 at sensitivity thresholds 0.90–0.99). Conclusions—: AF risk scores associate with cardioembolic stroke and exhibit moderate discrimination. Utilization of AF risk scores at the time of stroke may be most useful for identifying individuals at low probability of cardioembolism. Future analyses are warranted to assess whether stroke subtype classification can be enhanced to improve outcomes in undifferentiated stroke. Abstract : Supplemental Digital Content is available in the text.